Pemanfaatan Media Online PhET Simulation dalam Rangka Meningkatkan Pemahaman Konsep Fisika Siswa di SMAN 2 Sipora, Kecamatan Sipora Utara Kabupaten Mentawai - Irka, Feriska Handayani (LPPM UMRI, 2025)
Physics is still a subject that is less popular among high school students. Therefore, the physics curriculum should 1) guide teachers and students to the inquiry process to support students' achievement in learning science and 2) be designed to include fun experimental or observational activities for students. With today's sophisticated technology, physics experiments can be more easily accessed anywhere and anytime using a virtual laboratory. One of the free and easily accessible virtual laboratories for learning physics is PhET Colorado. The community service team from the Unand Physics Department designed a module related to experiments that is available on the PhET Colorado website and conducted online practicums at SMAN 2 Sipora. This community service activity aims to improve students' understanding of physics. About 90% of the students agreed and strongly agreed that activities like this benefit understanding the material in physics.